Fostering EFL Students’ Performance in English Syntax through Syntactic Tree Diagram Application - Dzakiah, Dzakiah; Asmawati, Nur (STAIN Majene, 2023)
This research seeks to investigate the effectiveness of using Syntactic Tree Diagram application to improve the students’ performance in English Syntax and the students’ interest in using the tool in English Syntax learning process. All participants were the sixth semester students of English Tadris Program of State Islamic University Datokarama Palu, Indonesia. This research was conducted through quasi experimental study design with two groups consisted of 18 students in the experimental group and 18 students in the control group. The instruments were syntax test to collect the data about the students’ performance in English Syntax and questionnaire to find out the students’ interest. After that, the data collections were analyzed using descriptive and inferential statistics through SPSS Program Version 23.0. The result of data analysis showed that (1) using Syntactic Tree Diagram application was more effective than drilling using the written tree diagram task to improve the students’ performance in English Syntax. It is seen from the significance t test result that reveals the significance value is lower than the significance level; 0.000 < 0.05. Furthermore, in relation to the students’ interest in using Syntactic Tree Diagram application to learn English Syntax, (2) it was found that the students’ interest in using the application was categorized as high.